2021
DOI: 10.3906/sag-2101-161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of extensively drug-resistant gram-negative bacteremia among solid-organ transplant recipients: a multicenter study

Abstract: Background/aim: The aim of this study is to evaluate the distribution, sources, clinical features, and mortality rates of bacteremia due to evaluation of extensively drug-resistant (XDR) gram negative among solid-organ transplant (SOT) recipients. Materials and methods:A retrospective study of SOT recipients with bacteremia due to XDR gram-negative pathogens in 11 centers between 2016 and 2018 was conducted. Patients' records were evaluated.Results: Of 171 bacteremia that occurred in 164 SOT recipients, 93 (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The CRE-associated mortality rate in SOT is consistent (up to 70%), as confirmed by The American Society of Transplantation Infectious Diseases Community [ 15 , 29 , 31 , 32 ]. Likewise, Yanik Yalçin et al [ 33 ] confirmed that the above-mentioned mortality rate was even higher in lung transplant recipients with CRE infections. With regards to MDR P. aeruginosa , a pretransplant colonization of the respiratory tract is especially common in lung transplant recipients with cystic fibrosis (CF), with a prevalence of 50% that may increase up to 75% after lung transplant [ 34 ].…”
Section: Multi-drug Resistant Gram-negative Bacteriamentioning
confidence: 90%
See 4 more Smart Citations
“…The CRE-associated mortality rate in SOT is consistent (up to 70%), as confirmed by The American Society of Transplantation Infectious Diseases Community [ 15 , 29 , 31 , 32 ]. Likewise, Yanik Yalçin et al [ 33 ] confirmed that the above-mentioned mortality rate was even higher in lung transplant recipients with CRE infections. With regards to MDR P. aeruginosa , a pretransplant colonization of the respiratory tract is especially common in lung transplant recipients with cystic fibrosis (CF), with a prevalence of 50% that may increase up to 75% after lung transplant [ 34 ].…”
Section: Multi-drug Resistant Gram-negative Bacteriamentioning
confidence: 90%
“…MDR GN bacteria isolation after transplantation is increasing, and no extended data are available regarding infections by XDR and PDR pathogens in lung transplant recipients. Although this, some findings could be extrapolated from previous retrospective studies and one case report [33,[36][37][38].…”
Section: Xdr and Pdr Bacteriamentioning
confidence: 92%
See 3 more Smart Citations